DEVELOPING METHOD OF DIFFERENTIAL PULSE POLAROGRAPHIC FOR ANALYSIS OF CHLORAMPHENICOL RESIDUE IN MILK - Daryono Hadi Tjahjono; Amir Musadad; Septy Mariana K (Universitas Gadjah Mada, 2004)
A differential pulse polarographic method for a quantitative analysis of chloramphenicol residue in milk had been developed. Result showed that the method using dropping mercury electrode as working electrode, Ag/AgCl electrode as reference electrode, and platinum electrode as auxiliary electrode with an acetic buffer solution of pH 4.7 as supporting electrolyte had a recovery for chloramphenicol of (96.88 ± 3.17)% with a detection limit of 0,027 µg/mL, a quantitation limit of 0,089 µg/mL, and a determination limit of 0,010 µg/mL.